Experiences of babies with written language - Moreira, Maria Fátima (2015)
The purpose of this study is to characterize the literacy experiences ofbabies aged between 14 and 24 months. In this study, four issues were analysed: which type of written language experiences are offered to the children, how parents value these literacy experiences, the way parents perceive their own role in the literacy development of their children and what parents know about their means of contributing to the literacy development of their children. Six mothers were interviewed. These interviews were analysed with the use of a categorical content analysis. The results suggest that mothers value and include in their practices facilitative and mediation actions of literacy experiences with their children, noting some variability depending on the respective qualifications.